O ensino da recepção estético-literária e a formação humana - Newton Duarte; Nathália Botura de Paula Ferreira; Maria Cláudia da Silva Saccomani; Mariana de Cássia Assumpção (EccoS – Revista Científica)
In this article are defended the possibility and the necessity of the teaching of the reception of art works in school education. Firstly, some relations between art and the development of both the human species and the individual are analysed in Georg Lukács and Lev Vygotsky's works. In order to put in question the old assumption that opposes education and instruction, the discussion made by Gramsci on the grammatical teaching of Latin and Greek in the traditional school education is explored. In the article is concluded its path analysing the intentional and systematic formation of the reception of art works provided by school education based on Aleksei N. Leontiev's works on the appropriation process of culture by the individual.